FRI0256 Ultrasound consensus definitions on normal and abnormal findings in salivary glands in sjÖgren's syndrome: results of an omeract delphi process. (15th June 2017) - Jousse-Joulin, S; Gandjbakhch, F; Ohrndorf, S; Backhaus, M; Tamborrini, G; Chary-Valckenaere, I; Terslev, L; Iagnocco, A; Collado, P; Hernandez-Diaz, C; Naredo, E; Schmidt, W; et al.
Abstract : Background: Ultrasonography (US) of salivary glands (USSG) may support diagnosis and evaluation of disease activity in primary Sjögren's syndrome pSS. In order to extent the use of USSG in daily practice, consensus definitions of normal and abnormal USSG findings are needed. Objectives: To obtain consensual definitions of normal and abnormal USSG findings using a Delphi process. Methods: Twenty-seven experts participated in the Delphi process. A Likert scale from 1–5 was used in which 1 indicated complete disagreement and 5 complete agreement. Three core items were proposed: 1. Consensus of assessment of SG (parotid gland (PG), submandibular glands (SMG), sublingual glands SLG)). 2. Consensus for elementary lesions of PG, SMG, and SLG changes in PSS patients. 3. Consensus on grading of PG, SM, and SLG in pSS. Results: The consensus of definitions between experts was reached after three rounds.The results (table 1 ) showed agreement with more than 75% of agreement in normal and abnormal definitions in SG and concluded to not evaluate SLG in pSS patients as well as to score pSS SG patients with at least two abnormal glands out of 4 (2 PG and 2 SMG) with a scoring system >2 for each abnormal gland. Conclusions: We developed a consensual US definition of normal and abnormal USGS findings through a Delphi exercise process. This finding will be used as a basis to further proceed with the validation of USGS for clinical application. Disclosure of Interest: None declared